Assignment of Motor Mechanics at the Tire Palace Using the Hungarian Method and Testing Software Quality Management (QM) - Widiarina, Widiarina; Mariskhana, Kartika; Sintawati, Ita Dewi (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Measurement of working time (time study) is basically an attempt to determine the placement of mechanical work from the length of work time required by a mechanic to complete a job. This study aims to place the optimal mechanical work in the context of service operational time efficiency and obtain optimal time savings that can be achieved by mechanics in working on motorcycle servicing so as to maximize income using the Hungarian Method. The purpose of this research is to optimize employee assignments by looking at the mechanical working time. The problems that occur at ISTANA BAN are the ineffectiveness of the work process time and the swelling of operational costs, especially in the work of Matic Kaburator, Injection Matic, Injection Duck, Kaburator Duck and Sport with 5 workers. The results of the Assignment Application with the Hungarian Method and Software Quality Management (QM) Testing, Evan mechanics serviced the Duck Kaburator motorbike with a service time of 25 minutes, Minus mechanic serviced the Injection Duck motorbike with a service time of 24 minutes, Hermon mechanic serviced the Sport motorbike with a service time of 27 minutes, mechanic Anton servicing the Matic Injection motorbike with a service time of 25 minutes, mechanic Zola servicing the Matic Kaburator motorbike with a service time of 26 minutes. After analyzing the possibilities, it can be concluded that all mechanics can service each type of motor if the assigned mechanic has worked on the specified type of motor. By minimizing mechanical service time, it will have an impact on Tire Zone revenue because the number of motorbikes being serviced is increasing. Total Tire Zone revenue can be increased from pre-implementation revenue using the Hungarian Method.